Industrial Relations and Job Satisfaction in the Provision of Healthcare Services to International Patients: A Conceptual Review - Ni Putu Dian Efriliana; R Tri Priyono Budi Santoso (Bali Tourism Journal, 2026)
The rapid growth of international tourism has increased demand for healthcare services for foreign patients, particularly in primary care clinics located in tourism-intensive regions. This development introduces complex organizational and workforce challenges, as healthcare workers are required to manage increased workloads, cross-cultural communication barriers, and expanded roles beyond routine clinical responsibilities. These conditions underscore the importance of industrial relations in shaping employee experiences and maintaining service sustainability. The purpose of this conceptual review is to examine how industrial relations influence job satisfaction among healthcare workers providing services to international patients, with particular attention to organizational support, communication practices, and leadership mechanisms in cross-cultural healthcare settings. This study adopts a conceptual review design by synthesizing theoretical and empirical literature related to industrial relations, job satisfaction, and international or tourism-oriented healthcare services. Relevant studies were retrieved from Scopus, Web of Science, PubMed, and Google Scholar and analyzed using thematic analysis. Social Exchange Theory and the Job Demands–Resources Model were employed as the primary theoretical frameworks to integrate findings and explain the relationship between job demands, organizational resources, and employee outcomes. No primary data were collected, and all conclusions are based on a systematic interpretation of existing literature. The review demonstrates that effective industrial relations function as a critical mediating mechanism that balances increased job demands associated with international patient care with available organizational resources. Strengthening leadership support, communication quality, and institutional recognition can enhance job satisfaction, reduce work strain, and contribute to sustainable healthcare service delivery in tourism-oriented environments.